Additional circular intercostal space created by bifurcation of the left 3rd rib and its costal cartilage: a case report - Kumar, Naveen (BioMed Central, 2013)
INTRODUCTION: In the thorax there are normally 11 pairs of intercostal spaces: the spaces between adjacent ribs. The intercostal spaces contain intercostal muscles, intercostal nerves and vessels. CASE PRESENTATION: During a routine dissection for undergraduate medical students, we observed a variation involving the left 3rd rib and 3rd costal cartilage in the cadaver of a man of Indian ethnicity aged about 65 years. The left 3rd rib and its costal cartilage were bifurcated at their costochondral junction enclosing a small circular additional intercostal space. Muscle tissue covered by deep fascia was present in this circular intercostal space. The muscle in the circular intercostal space received its nerve supply from a branch of the 2nd intercostal nerve. CONCLUSIONS: Knowledge of such variations is helpful to surgeons operating on the anterior thoracic wall involving ribs and intercostal spaces. Knowing the possibility of the presence of an additional space between normal intercostal spaces can guide a surgeon through to a successful surgery.